Learning Physics of Motion and Force Using the Outdoor Activities: An Effort to Increase Students’ Interest and Achievement at Secondary School - Djajadi, M.; Rauf, A. (Jurnal Pendidikan IPA Indonesia, 2020)
This study aimed to determine the increase in students’ interest and achievement of science in the 8th graders of SMP Negeri 1 Watampone, Bone Regency Indonesia, when using outdoor activities. This study applied Classroom Action Research (CAR), which consists of two learning cycles following the procedural phase such as planning, implementation, observation phase, and reflection. The sample was taken using a purposive sampling technique class. The data collected included data about the students’ science achievement before the implementation of the action, data about the students’ interest in learning science, data about the students’ science achievement in the cycle I and cycle II, and data on the observations/notes of the teacher in each research cycle. Data were obtained through a questionnaire asking about students’ interest in learning science, students’ achievement result test before the implementation of the action, students’ achievement test in cycle I and cycle II, and student learning observation sheet. Data then analyzed using quantitative and qualitative descriptive analysis techniques. The results showed that there was an increase in students’ achievement, both in cycle I and in cycle II. Students’ mastery level in science materials was in the high category and their readiness, sincerity, and activeness in participating in the learning process were increased. Recommendation and direction for further research are included in the study.